2020
DOI: 10.1016/j.pharma.2020.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Impact on mental health of the COVID-19 outbreak among community pharmacists during the sanitary lockdown period

Abstract: Highlights This study showed the psychological impact of COVID-19 in community pharmacists. Up to 35% of pharmacists reported psychological disturbances. Interventions to promote mental well-being of healthcare workers need to be developing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
55
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 17 publications
3
55
0
2
Order By: Relevance
“…The difference between our findings and those of other previously published studies is all the more significant because we used a threshold of = 40 IES-R points, as recommended in France, instead of the threshold of = 24 or 26 points employed in the previous studies. However, our results are consistent with the 16% to 27% incidence of PTSD obtained with various evaluation scales (IES-R, Post-traumatic Stress Disorder Checklist for DSM-5) among French ICU professionals and pharmacists [4] , [5] , [10] .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The difference between our findings and those of other previously published studies is all the more significant because we used a threshold of = 40 IES-R points, as recommended in France, instead of the threshold of = 24 or 26 points employed in the previous studies. However, our results are consistent with the 16% to 27% incidence of PTSD obtained with various evaluation scales (IES-R, Post-traumatic Stress Disorder Checklist for DSM-5) among French ICU professionals and pharmacists [4] , [5] , [10] .…”
Section: Discussionsupporting
confidence: 90%
“…Several studies conducted in China during the SARS-CoV-2 outbreak and previous studies conducted during the Severe Acute Respiratory Syndrome (SARS) et Middle East Respiratory Syndrome (MERS) epidemics revealed high levels of anxiety, depression and post-traumatic stress disorders (PTSD) among healthcare professionals [1] , [2] . In France, studies have evaluated the psychological impact of the SARS-CoV-2 epidemic on specific populations, such as intensive care unit (ICU) healthcare professionals [3] , [4] , [5] , radiologists [4] , residents in oncology, radiotherapy, urology and surgery [7] , [8] , [9] , community pharmacists [10] and professionals working in acute care geriatric facilities [11] . However, global data on the psychological impact of the SARS-CoV-2 epidemic on hospital staff are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Our study represents one of the first published studies that, to our knowledge, analyzes COVID-19’s impact on quality of life among pharmacists in Romania and Bulgaria. We found only one study that underlined the pressure that community pharmacists are subjected to during lockdown [ 36 ]. Our work also stands as a comparison between two neighboring countries regarding psychological disturbance in community pharmacists, as front-line health-care workers.…”
Section: Discussionmentioning
confidence: 99%
“…The mental health impact of COVID-19 pandemic has been noticed in more than 50% of pharmacists, and some studies even highlighted higher rates of burnout among pharmacists in comparison with nurses and physicians [35]. Another study, conducted by Lange et al [36], showed that approximately 35% of community pharmacists reported mental health disturbances (anxiety, stress, insomnia, sense of losing control, fear, hopelessness [37]), with females being more affected [36]. These results, coming from the very first studies analyzing the psychological impact of COVID-19 pandemic among community pharmacists, in the French region of Normandy [37], are not consistent with our results because of the different period of the studies.…”
Section: Discussionmentioning
confidence: 99%
“…Abundant professional knowledge is the basis for clinical pharmacists to gain a rm foothold in treatment teams [6]. Second, we need to provide platform support, spiritual support [23], and increase the clinical pharmacists' participation in team-based care [26,27]. The work of clinical pharmacists is increasingly recognized by the medical team.…”
Section: Discussionmentioning
confidence: 99%